A Molecular Turnstile as an E‐Field‐Triggered Single‐Molecule Switch: Concept and Synthesis. Issue 22 (9th June 2017) - Le Pleux, Loïc; Kapatsina, Elisabeth; Hildesheim, Julia; Häussinger, Daniel; Mayor, Marcel
Abstract : A new single‐molecule switching concept relying on the E ‐field‐dependent orientation of a push‐pull system (via its dipole moment) is presented. As first steps towards realizing the E ‐field‐triggered single‐molecule motion, the synthesis of turnstile1, which is designed to bridge a gap within a carbon nanotube junction, is reported. Turnstile1 consists of a hexakis( m ‐phenyleneethynylene) macrocycle decorated with phenanthrene‐functionalized oligo(phenyleneethynylene) (OPE) wires at opposite ends, as well as a para ‐connected push‐pull rod as rotator unit. The similarity of the rotor dimension with the surrounding macrocycle guarantees efficient π‐stacking between both subunits when an E ‐field is applied. To introduce a dipole moment into the rotator, the structure is terminally functionalized with a nitrile group on one side and with a dimethylamino group on the opposite end. Synthetic protocols based on Sonogashira–Hagihara couplings were developed to build up the macrocycle scaffold. The highly functionalized open precursorA is the key building block of the sequence as it allows a twofold intramolecular palladium‐catalyzed cyclization reaction to be performed to obtain the target turnstile in a very good yield of 68 %. The target structure was fully characterized by NMR spectroscopy and mass spectrometry. Furthermore, 1 H‐ 1 H NOESY NMR experiments pointed to a pseudo‐rotation of the push‐pull rod within the turnstile structure on the time scale of the NMR experiment. Abstract : Like in an old mechanical electrical switch, an applied E ‐field is used to trigger an intramolecular rotation in the turnstile structure, thereby altering its electronic transparency. The switching mechanism of the turnstile model compound reported here is not only in the focus of interest as an electronic switch, but also as a single‐molecule mechanical molecular machinery experiment.